Elucidating the Role of TP53 in Oral Squamous Cell Carcinoma: A Cross-Sectional Observational Study of Integrated Analysis of Expression Patterns and Functional Importance - S., Sneha Harshini; KP, Ameya; PP, Ashikha S. Usman; Sekar, Durairaj (Indian Journal of Medical and Paediatric Oncology, 2025)
Oral squamous cell carcinoma (OSCC) is one of the major contributors of cancers associated with carcinoma, specifically among alcohol and tobacco consumers. Alterations in the TP53 gene are known to contribute to aggressive features of tumors. The present study explores miR-21, a microRNA targeting TP53 gene, focusing on the potential role of miR-21 in the regulation of OSCC pathogenesis at both computational and experimental levels.This article aims to evaluate the expression and regulatory relationship between miR-21 and TP53 in OSCC, and to determine the potential of miR-21 as a therapeutic target.This was a cross-sectional observational study designed to investigate the regulatory relationship between miR-21 and TP53 gene in OSCC. A total of 30 OSCC tissue samples and normal tissue samples were collected from patients undergoing surgical resection at Saveetha Dental College and Hospitals, following approval by the institutional ethics committee and after obtaining informed consent. Tissue specimens were immediately snap-frozen in liquid nitrogen and stored at −80 °C until further use.The bioinformatics tools, TargetScan and miRDB, predicted the miRNAs that regulate TP53. The OSCC tissue samples were used to perform qRT-PCR following the extraction of RNA with TRIzol reagent for the expression profiling of miR-21 and TP53 gene.While TP53 gene expression was noticeably downregulated, the research showed that miR-21 was considerably increased in OSCC tissues. Given their inverse association, miR-21 may enhance carcinogenesis by suppressing TP53 activity.The findings underscore the critical interplay between miR-21 and TP53 in OSCC pathogenesis. By regaining TP53 function, targeting miR-21 may offer a cutting-edge therapeutic approach for bettering patient outcomes. The clinical consequences of these interactions should be investigated further to provide tailored treatments for the management of OSCC.
Keywords: oral squamous cell carcinoma; microRNAs; gene expression; computational biology; biomarker